Using fish models to investigate the links between microbiome and social behaviour: The next step for translational microbiome research?. Issue 4 (26th April 2019) - Soares, Marta C.; Cable, Jo; Lima‐Maximino, Monica G.; Maximino, Caio; Xavier, Raquel
Abstract: Recent research has revealed surprisingly important connections between animals' microbiome and social behaviour. Social interactions can affect the composition and function of the microbiome; conversely, the microbiome affects social communication by influencing the hosts' central nervous system and peripheral chemical communication. These discoveries set the stage for novel research focusing on the evolution and physiology of animal social behaviour in relation to microbial transmission strategies. Here, we discuss the emerging roles of teleost fish models and their potential for advancing research fields, linked to sociality and microbial regulation. We argue that fish models, such as the zebrafish ( Danio rerio, Cyprinidae), sticklebacks (‎Gasterosteidae), guppies (Poeciliidae) and cleaner–client dyads (e.g., obligate cleaner fish from the Labridae and Gobiidae families and their visiting clientele), will provide valuable insights into the roles of microbiome in shaping social behaviour and vice versa, while also being of direct relevance to the food and ornamental fish trades. The diversity of fish behaviour warrants more interdisciplinary research, including microbiome studies, which should have a strong ecological (field‐derived) approach, together with laboratory‐based cognitive and neurobiological experimentation. The implications of such integrated approaches may be of translational relevance, opening new avenues for future investigation using fish models.